Eksplorasi Pengaruh Jenis Kelamin dalam Menyelesaikan Soal HOTS IPA pada Sekolah Dasar di Kabupaten Kediri. - Widyaningrum, Septi; Handayanto, Supriyono Koes; Anggraini, Ade Eka (Universitas Nahdlatul Ulama Blitar, 2025)
This research aimed to determine the high-level thinking skills of sixth-grade elementary school students in answering HOTS questions in science subjects. The research method used was quantitative descriptive. The data collection technique was using test techniques. The research sample was sixth-grade students in Wates sub-district, Kediri Regency who had completed the magnet material with a sample size of 243 students. The collected data were analyzed using SPSS. The critical thinking skills of elementary school students in Kediri Regency in solving HOTS science questions were included in the sufficient category with an average of 49.03. The average for female students in solving HOTS science questions was 48.20 while male students obtained an average of 49.84. T-test and correlation data from SPSS stated that gender differences were not a factor that influenced students' abilities in solving HOTS questions.